فاعلية برنامج إرشاد جمعي في خفض العود إلى الجريمة لدى نزلاء السجن المركزي في سلطنة عمان - خروصي، طلال ناصر سالم (Kulliyah of Education, International Islamic University Malaysia, 2020)
The CORNET study aimed to build a collective guidance program and investigate its effectiveness in reducing the return to crime among the inmates of the Central Prison in the Sultanate of Oman. The study pattern consists of 40 inmates returning to drug offenses. The Experimental approach was used by creating two groups, an experimental group consists of 20 inmates who applied a collective guidance program and a control group consist of 20 inmates who receive no treatment. The program consisted of 17 sessions within eight weeks, with two guiding sessions per week, the duration of each session lasted for 50-90 minutes. In order to verify the equivalence of the two study groups, the T-test was used in the pre-test, to test the hypotheses of the study, the means, and standard deviations of the experimental and control group scores were calculated In the Scale of return to Crime and in each of its three fields for the post-test. The multivariate analysis (MANOVA) results showed that there were statistically significant differences at the level of (α ≤ 0.05) between the experimental group and the control group in the overall degree of the post- test in the scale of return to the crime and in all its fields for the favor of the experimental group. Where (Wilks' Lambda) value approached (0.195) reached at the level of less than (0.001); this indicates that the guidance program is effective in reducing the level of return to crime. Furthermore, the results showed that the impact of the guidance program on the experimental group reached (3, 82); according to Cohen's standard, the effect is significant. The results also showed that there were statistically significant differences in the degree of return to crime among the experimental group in the both pre and post- tests at the level of (α ≤ 0.05) In favor of the post- test due to the guidance program used in the study. The results also showed no statistically significant differences at the level of (α ≤ 05) for the experimental group on the total score of the scale and for each field in both pre and post - test, indicating that the guidance program used in this study will still be effective after a period of sufficient time.